Radiation Recall Dermatitis following Radioactive Iodine Therapy: A New Observation - Ikechukwu Chidobem; Tahereh Orouji Jokar; Chisom Mgbodile; Francis Mgbodile; Ghassan Bassil; Nazia Khan (Case Reports in Oncological Medicine)
A 47-year-old female, who had previously received adjuvant right breast radiation for ductal carcinoma in situ, presented with right breast edema, erythema, and pain. This developed about two and a half weeks following radioactive iodine therapy for thyroid carcinoma. A biopsy was performed to rule out malignancy, since inflammatory breast cancer can present with similar symptoms. This confirmed radiation recall dermatitis (RRD) as the most likely diagnosis. RRD is an inflammatory reaction occurring in a previously irradiated field and was first described in 1959. Subsequent reports in the literature have associated it with the administration of other drugs, mostly chemotherapy. To our knowledge, this is the first reported case of RRD following radioactive iodine therapy.